Kekerabatan Genetik Tanaman Jambu Bol (Syzygium malaccense [L.] Merr. & Perry) Berdasarkan Penanda RAPD (Random Amplified Polymorphic DNA) (Jurnal Agro Teknologi Tropika, 2013)
Jambu bol (Syzygium malaccense [L.] Merr. & Perry) has significant economic value, as a fruit crop and medicinal plants.This research aims to study the level of genetic diversity and relationship among S. malaccense crops from Kampar districtbased on RAPD marker. Six cultivars of S. malaccense were analyzed using ten random primers. The results of this researchshowed that ten selected primers produced 219 fragments of DNA band ranging from 188-2028 bp. The genetic diversity of S.malaccense is 0.304, and the genetic distances among cultivars ranges from 0.253 to 0.631. Based on UPGMA dendogram, S.Malaccense can be divided into four groups. The first group of S. malaccense is without seeds (JTB), second group is S.malaccense red fruits (JBM), S. malaccense local (JKL) and S. malaccense with greenish white fruits (JPK), third group is S.malaccense white fruits (JBP) and last group is S. malaccense small leaves (JDK). The result of this study can be utilized bybreeders to formulate the genetic improvement program of S. malaccense in the future.Key words: genetic relationship, Syzygium malaccense, RAPD marker